2015
DOI: 10.1371/journal.pntd.0003862
|View full text |Cite
|
Sign up to set email alerts
|

Snake Cathelicidin NA-CATH and Smaller Helical Antimicrobial Peptides Are Effective against Burkholderia thailandensis

Abstract: Burkholderia thailandensis is a Gram-negative soil bacterium used as a model organism for B. pseudomallei, the causative agent of melioidosis and an organism classified category B priority pathogen and a Tier 1 select agent for its potential use as a biological weapon. Burkholderia species are reportedly “highly resistant” to antimicrobial agents, including cyclic peptide antibiotics, due to multiple resistance systems, a hypothesis we decided to test using antimicrobial (host defense) peptides. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 56 publications
4
43
0
Order By: Relevance
“…For both of them, minimal biofilm inhibitory concentration (MBIC) values ranging from 8 to 35 µg/mL against five clinical strains of P. aeruginosa have been obtained [95]. Moreover, Blower et al [86] demonstrated that the SMAP-29 peptide is able to inhibit biofilm production in Burkholderia thailandensis by about 50% at peptide concentrations at or above 3 µg/mL. Anunthawan et al studied KT2 and RT2, two synthetic tryptophan-rich cationic peptides, which showed activity against multidrug-resistant E. coli biofilms at sub-MIC levels [96].…”
Section: Antimicrobial Peptides and Biofilmmentioning
confidence: 99%
“…For both of them, minimal biofilm inhibitory concentration (MBIC) values ranging from 8 to 35 µg/mL against five clinical strains of P. aeruginosa have been obtained [95]. Moreover, Blower et al [86] demonstrated that the SMAP-29 peptide is able to inhibit biofilm production in Burkholderia thailandensis by about 50% at peptide concentrations at or above 3 µg/mL. Anunthawan et al studied KT2 and RT2, two synthetic tryptophan-rich cationic peptides, which showed activity against multidrug-resistant E. coli biofilms at sub-MIC levels [96].…”
Section: Antimicrobial Peptides and Biofilmmentioning
confidence: 99%
“…AMPs have made a big impact in antimicrobial research, to diminish the inefficacy of antimicrobial therapy in immunocompromised hosts and also ongoing emergence of resistance to conventional antibiotics worldwide (Giuliani, Pirri & Nicoletto, 2007). Among the AMPs which were reported to demonstrate potential to inhibit B. pseudomallei include LL-37 (Kanthawong et al, 2012), PG1 (Sim et al, 2011), bovine lactoferrin (Puknun et al, 2013), phospholipase A2 (Samy et al, 2015), and SMAP-29 (Blower, Barksdale & van Hoek, 2015). However, there are more potential AMPs that are yet to be tested against B. pseudomallei .…”
Section: Discussionmentioning
confidence: 99%
“…Groups of AMP’s i.e., defensins, cathelicidins, and dermicins have previously been reported to show potential against various pathogens (Wiesner & Vilcinskas, 2010). However, to date, only a few cathelicidin AMPs have been reported to be effective against B. pseudomallei, including LL-37 (Kanthawong et al, 2012), protegrin 1 (PG1) (Sim et al, 2011), bovine lactoferrin (Puknun et al, 2013), phospholipase A2 inhibitors (Samy et al, 2015), and sheep cathelicidin (SMAP-29) (Blower, Barksdale & van Hoek, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was further confirmed in vitro by Gupta el al. and Juba et al, who described membrane depolarization and transient-pore formation in Mycobacterium smegmatis [103], as well as in E.coli and B. cereus [119] after Na-CATH treatment. However, Samuel et al suggested a more detailed mechanism changing from membrane disruption to pore-based lysis, depending on liposome lipid composition and phase [120].…”
Section: Sourcementioning
confidence: 95%
“…• Na-CATH: this CATH from the venom gland of the Chinese cobra N. atra [76] also demonstrated powerful, salt-resistant, antimicrobial activity against Gram-positive and Gram-negative bacteria, including Francisella novicida (the non-virulent strain in humans related to Francisella tularensis, the causative agent of tularemia) [98], E.coli, Aggregatibacter actinomycetemcomitans, Bacillus cereus [99], P. aeruginosa [100], and S. aureus [101] at low concentrations (EC 50 < 3 µg/mL). Na-CATH is also active against Mycobacterium smegmatis [102], Burkholderia thailandensis (closely related to B. pseudomallei, the causative agent of melioidosis) [103] and Bacillus anthracis (anthrax) [104]. The last two strains are of particular relevance due to their potential use as biological weapons.…”
Section: Sourcementioning
confidence: 99%